EVALUATION OF THE THEORETICAL DESIGN AND MATHEMATICAL MODELING FOR DETERMINATION OF THERMAL AND VISCOUS IRREVERSIBILITIES IN AXIALLY FINNED TWO-PHASE CLOSED THERMOSYPHON HEAT EXCHANGER - Nogueira, Élcio; dos Santos Filho, Diniz Felix; Felix, Ryan; Tavares, Eliseu Luan de O. (Seven Editora, 2025)
Heat exchangers using thermosyphons have been used for decades in various applications in the aeronautical, military, nuclear, and electronics industries. One application that has gained recent interest, despite having been proposed around 1992, is thermal comfort in air conditioning systems. In this paper, we present a heat exchanger design that uses axially finned thermosyphons - AFTHE. The current design uses a radially finned heat pipe heat exchanger as a reference, whose theoretical and experimental analysis is already well established. Mathematical modeling applies to the thermal efficiency method to determine quantities of thermal interest, and the second law of thermodynamics, with an emphasis on the Bejan number, to determine thermal and viscous irreversibilities. Numerical and graphical results are determined and presented for the following physical quantities: velocities, Reynolds numbers, Nusselt numbers, convection heat transfer coefficients, number of thermal units, heat transfer rates, friction factors, pressure drops, and Bejan number. The results are used for theoretical analyses of the heat exchanger's evaporator and condenser, demonstrating the expected physical consistencies for all analyzed quantities. To consolidate the heat exchanger theoretical design and the applied  theoretical model, a comparison is presented for the air outlet temperatures and effectiveness, using theoretical-experimental results obtained for the radial-fin heat exchanger, in the evaporator, and the condenser. The comparisons made demonstrate that the axially finned tube design presents better thermal performance with a lower heat exchange area than the radially finned heat pipe design, for the same inlet conditions. The current design presents promising results and should be used in the experimental implementation of an air conditioning system for surgical rooms.DOI: https://doi.org/10.56238/sevened2025.036-128